2022
DOI: 10.1186/s13287-021-02675-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 coaxes cellular dedifferentiation as a pro-regenerative intermediate that contributes to pericardial ADSC-induced cardiac repair

Abstract: Background Cellular dedifferentiation is a regenerative prerequisite that warrants cell cycle reentry and appropriate mitotic division during de novo formation of cardiomyocytes. In the light of our previous finding that expression of injury-responsive element, Wilms Tumor factor 1 (WT1), in pericardial adipose stromal cells (ADSC) conferred a compelling reparative activity with concomitant IL-6 upregulation, we then aim to unravel the mechanistic network that governs the process of regenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In the present experiments, we showed that cardiac commitment occurred in an in vivo scenario in which the pericardial layer expanded in cell numbers and adhered to the heart surface after MI ( Figure 1A ). After isolation, pSCs were demonstrated to be phenotypically identical to mesenchymal stem cells with minimal contamination of hematopoietic and endothelial lineages ( Wang et al, 2014 ; Tang et al, 2018 ; Zhu et al, 2022 ). After myogenic induction in vitro , pSCs formed myoblast-like clusters and gave rise to cardiac lineage under low-serum cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present experiments, we showed that cardiac commitment occurred in an in vivo scenario in which the pericardial layer expanded in cell numbers and adhered to the heart surface after MI ( Figure 1A ). After isolation, pSCs were demonstrated to be phenotypically identical to mesenchymal stem cells with minimal contamination of hematopoietic and endothelial lineages ( Wang et al, 2014 ; Tang et al, 2018 ; Zhu et al, 2022 ). After myogenic induction in vitro , pSCs formed myoblast-like clusters and gave rise to cardiac lineage under low-serum cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that pericardial tissue harbors a stem cell pool, known as pSCs, that, trained by inflammatory signaling, evolved into a specialized population with boosted reparative activity and myogenic potential ( Tang et al, 2018 ; Zhu et al, 2022 ; Zhu et al, 2023 ). However, we found that the cardiac benefits of the transplanted pSCs were solely mediated by paracrine factors released, whereas the pre-committed cells were poorly retained in the heart and negligibly converted into cardiomyocytes in vivo ( Tang et al, 2018 ; Zhu et al, 2022 ). To this end, it is of particular interest to determine whether pSCs after cardiac commitment are able to survive and stably engraft in the recipient heart as well as the differentiated CMs derived from pluripotent stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…After validation using GEO datasets and MI mice model, the 10 hub genes, such as IL-6, PTGS2, JUN, NQO1, NOS3, LEPR, NAMPT, CDKN2A, CDKN1A, and Snai1, can be the diagnostic ferroptosis- and autophagy-related targets and biomarkers in MI deterioration and can be targets to prevent adverse cardiac events. IL-6, as a protective cytokine, promoted cellular dedifferentiation and led to pericardial ADSC-induced cardiac repair ( 32 ). Higher IL-6 levels were independently correlated to the risk of major adverse cardiovascular events (MACE), and elevated IL-6 level was associated with an increased risk of MACE at normal kidney function, mild chronic kidney disease (CKD), and moderate to severe CKD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) stimulates chronic inflammation and regulates the expression of C-reactive protein and cardiovascular disease risk biomarker [ 47 ]. IL-6 is related to angiotensin II (Ang-II)-mediated hypertension [ 48 ].…”
Section: Potential Mechanisms Of Comorbid Hypertension and Anxietymentioning
confidence: 99%